2014
DOI: 10.1186/1423-0127-21-10
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-containing bisphosphonates inhibit RANKL- and M-CSF-induced osteoclast formation through the inhibition of ERK1/2 and Akt activation

Abstract: BackgroundBisphosphonates are an important class of antiresorptive drugs used in the treatment of metabolic bone diseases. Recent studies have shown that nitrogen-containing bisphosphonates induced apoptosis in rabbit osteoclasts and prevented prenylated small GTPase. However, whether bisphosphonates inhibit osteoclast formation has not been determined. In the present study, we investigated the inhibitory effect of minodronate and alendronate on the osteoclast formation and clarified the mechanism involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…The lack of significant decrease in OC viability upon treatments by pamidronate or alendronate in their free form [Figure (A)] agree with the report by Martins et al wherein differentiated Raw 264.7 cells showed a decrease in cell viability only when treated with a concentration of 10 μ M or larger of alendronate. Additionally, Tsubaki et al reported a decrease in cell viability at 5 µ M of alendronate and above, though they used the C7 osteoclast cell line, which suggests that the threshold is sensitive to the cell line. The lack of significant decrease in OC viability upon treatment with gold nanoparticles alone indicates that GNPs likely have no significant effects on the viability of these cell lines when they are not conjugated with BPs and this result is in agreement with what is typically reported in literature about the low toxicity of GNPs on mammalian cells .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of significant decrease in OC viability upon treatments by pamidronate or alendronate in their free form [Figure (A)] agree with the report by Martins et al wherein differentiated Raw 264.7 cells showed a decrease in cell viability only when treated with a concentration of 10 μ M or larger of alendronate. Additionally, Tsubaki et al reported a decrease in cell viability at 5 µ M of alendronate and above, though they used the C7 osteoclast cell line, which suggests that the threshold is sensitive to the cell line. The lack of significant decrease in OC viability upon treatment with gold nanoparticles alone indicates that GNPs likely have no significant effects on the viability of these cell lines when they are not conjugated with BPs and this result is in agreement with what is typically reported in literature about the low toxicity of GNPs on mammalian cells .…”
Section: Resultsmentioning
confidence: 99%
“…For the free bisphosphonates, osteoclasts were treated with 1–5 μ M of bisphosphonates and as one‐half the seeding density was used in case of osteoblasts, the concentration was reduced to 0.5 to 2.5 μM. These treatment concentrations are comparable to concentrations (1 nM −10 µM) that have been used in other in vitro studies . In the case of samples treated with gold nanoparticle systems, treatment with 10–50 μL of nanoparticle solution was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding of the molecular mechanisms involved in promoting bone density has been important to the development of multiple drug therapies for osteoporosis, such as the capthepsin K inhibitors Odanacatib (Eisman et al, 2011) and Balicatib (Adami et al, 2006), anti-SOST antibodies (Padhi et al, 2011), anti-Dkk1 antibodies (Hoeppner et al, 2009), and GSK3β and Sfrp1 inhibitors (Kulkarni et al, 2006; Moore et al, 2009). Bisphosphonates, a standard treatment used in osteoporosis, function to decrease osteoclast-mediated bone resorption (Tsubaki et al, 2014). Previous in vitro studies have suggested that osteocalcin might recruit osteoclast precursors and increase subsequent differentiation of these cells into osteoclasts (Malone et al, 1982; Mundy and Poser, 1983; Chenu et al, 1994), suggesting that osteocalcin might be a novel target for treating osteopenia or osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…36 BP-based drugs are known to inhibit mature osteoclasts from attaching to the bone surface by altering the cytoskeleton and subsequent loss of the ruffled borders, thereby slowing down resorption. 45 In order to verify if the effect is replicable with a drug delivery vehicle that does not present suitable ligands for receptormediated uptake, we used bisphosphonated PVA. Indeed, this adduct had no detectable effect on the survival of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%